Economic growth evens-out happiness: Evidence from six surveys - Andrew E. Clark; Sarah Fléche; Claudia Senik (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
In spite of the great U-turn that saw income inequality rise in Western countries in the 1980s, happiness inequality has dropped in countries that have experienced income growth (but not in those that did not). Modern growth has reduced the share of both the very unhappy and the perfectly happy. The extension of public amenities has certainly contributed to this greater happiness homogeneity. This new stylized fact comes as an addition to the Easterlin paradox, offering a somewhat brighter perspective for developing countries.
Keywords: D31; D6; I3; O15; 330; happiness; inequality; economic growth; development; Easterlin paradox